Upaya Meningkatkan Pendidikan Masyarakat Di Daerah Terpencil - Safiq Maulido; Popi Karmijah; Vinanda Rahmi (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This article discusses various efforts that have been made to improve the quality of education in remote areas. In facing the challenges of accessibility and limited resources, innovative and strategic approaches have been implemented. This article explores the implementation of non-formal education programs, collaboration between stakeholders, and the use of technology to overcome these obstacles. By detailing the concrete steps that have been taken, this article provides insight into how to effectively improve education in remote areas to create better accessibility and quality of education. The step that can be taken is to follow existing technological developments, where rapid technological developments have had a significant impact on the education sector in Indonesia. This article reviews how advances in technology, especially digital technology, have formed a new paradigm in learning. The use of technology as a means of communication in the learning process has changed the way educators and students interact. Educators need to adapt to this new habit to create an interesting, effective and efficient learning environment, as well as provide comfort to students.